1981
DOI: 10.1117/12.7972819
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Fabry-Perot Filters

Abstract: There has been considerable interest in recent years in the development of electronically tunable optical spectral filters. The applications for these filters range from rapid -scan spectrometry to multispectral imaging in remote sensor systems. The requirements on the characteristics of these filters include: moderate spectral resolution and high out -of -band rejection large field of view large optical aperture and high optical transmission electronic tunability with wide tuning range and rapid tuning rate.P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
3

Year Published

1988
1988
2021
2021

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(97 citation statements)
references
References 0 publications
1
93
0
3
Order By: Relevance
“…The buckling self-assembly produces cavities with a high degree of geometrical perfection, characterized by cylindrically symmetric Laguerre-Gaussian modes and reflectance-limited finesse. Recently, Potts et al reported arrays of these microcavities [16] with SiO2/Ta2O5 Bragg mirrors, and exhibiting F ~ 3500 and mode volume ~ 35λ 3 . These cavities were designed for operation near 780 nm wavelength, and could be thermally tuned to the D2 transition of Rb.…”
Section: Chip-based Fpcs For Cqedmentioning
confidence: 99%
“…The buckling self-assembly produces cavities with a high degree of geometrical perfection, characterized by cylindrically symmetric Laguerre-Gaussian modes and reflectance-limited finesse. Recently, Potts et al reported arrays of these microcavities [16] with SiO2/Ta2O5 Bragg mirrors, and exhibiting F ~ 3500 and mode volume ~ 35λ 3 . These cavities were designed for operation near 780 nm wavelength, and could be thermally tuned to the D2 transition of Rb.…”
Section: Chip-based Fpcs For Cqedmentioning
confidence: 99%
“…Light reflects and refracts multiple times between the two plates resulting in the multi-beam interference [10]. In general, for an interferometer, the distance between the two plates may change, but it is a constant for an etalon.…”
Section: Principlementioning
confidence: 99%
“…The theory of Fraunhofer filter design is reviewed i n Ref. 5 and a practical example is described in Ref. 6.…”
Section: B Fraunhofer Filtermentioning
confidence: 99%